2015
DOI: 10.1136/bcr-2015-212621
|View full text |Cite
|
Sign up to set email alerts
|

Late quadriceps tendon rupture at the donor site following cruciate ligament reconstruction using central quadriceps tendon graft

Abstract: Central quadriceps tendon (CQT) graft has been successfully used as a viable autograft option in cruciate ligament reconstruction of the knee. The prime emphasis in the majority of the literature is given to surgical details of quadriceps graft harvesting and outcome of cruciate ligament reconstruction. There is less discussion about donor site morbidity in CQT graft, and it is less frequent as compared to that in bone patellar tendon bone graft. We report an extremely unusual case of late quadriceps tendon ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Chen et al reported that 9 % of subjects exhibited donor site pain after quadriceps graft harvesting, and the risk of occult partial rupture of the remaining quadriceps tendon may exist. Late quadriceps tendon rupture at the donor site following harvesting of a quadriceps tendon graft has been reported (Pandey et al 2015). Loss of quadriceps muscle strength of 20 % after harvesting the quadriceps tendon graft for anterior cruciate ligament reconstruction and prolonged weakness of knee extension strength, predominantly in women, have also been reported (Chen et al 2006;Yasuda et al).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that 9 % of subjects exhibited donor site pain after quadriceps graft harvesting, and the risk of occult partial rupture of the remaining quadriceps tendon may exist. Late quadriceps tendon rupture at the donor site following harvesting of a quadriceps tendon graft has been reported (Pandey et al 2015). Loss of quadriceps muscle strength of 20 % after harvesting the quadriceps tendon graft for anterior cruciate ligament reconstruction and prolonged weakness of knee extension strength, predominantly in women, have also been reported (Chen et al 2006;Yasuda et al).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report of delayed-onset QT ruptures has been described in ACL reconstruction with adult QTs. 21…”
mentioning
confidence: 99%
“…Donor-site quadriceps tendon rupture following QT ACL-R is an extremely rare complication; only two occurrences have been published in the literature at the time of writing. A 2015 case shared an instance of QT rupture 10 years following combined ACL and posterior cruciate ligament reconstruction, which were performed with QT and quadrupled-hamstrings graft, respectively [62]. One instance of QT rupture four years after QT ACL-R was reported in a 2020 retrospective cohort study [16].…”
Section: Discussionmentioning
confidence: 99%
“…Donor‐site quadriceps tendon rupture was defined by imaging‐diagnosed physical tear of the remnant quadriceps tendon at the harvest site [62]…”
Section: Discussionmentioning
confidence: 99%